REPLACEMENT VALUE ENGINEERING MATERIAL (AC BASE, AGGREGATE A AND AGGREGATE B) A CTB ON THE ROAD MAINTENANCE WORK PACKAGE WARU - TAMAN -KRIAN BY PASS WITH AASHTO 1993 METHOD - Sulihanto A.W, R. Agus (Universitas 17 Agustus 1945 Surabaya, 2013)
With the current economic conditions , construction projects are required to work more pressure oncosts while maintaining the quality of the project . One alternative that is applied to achieve the requiredfunctions with optimal cost and the end result is Value Engineering . The purpose of this study to applyValue Engineering in construction projects . One project in the works is a Road Maintenance Project Waru -Taman - Krian Bypass. Value engineering is a creative way and planned approach in order to identify andstreamline costs unnecessary . Value engineering is used to find an alternatives or ideas which aim to producea better cost / lower than previously planned with functional limitations and quality of the work . Applicationof Value Engineering work done on Aggregate Base . Value Engineering Analysis performed on RoadMaintenance Project Waru - Taman - Krian By Pass. The problem studied is how to bring out the alternativesas a substitute on the job Aggregate Base . This study aims to determine the amount of cost savings thatoccur after the implementation of the Value Engineering Aggregate base layer A , B with CTB. Measures ofValue Engineering work is composed of four (4) phases: the high cost of information includes theidentification and identification of unnecessary cost ( analysis function ) ; creative stage ; analysis phaseincludes the selection of alternative with profit and loss analysis , cost analysis of alternatives to stage of theproject life cycle as well as recommendations. By comparing construction costs between the base layerconstruction Aggregate Aggregate A and B with the construction of the foundation layer using CTB , thenthe cost is obtained as follows : a. The cost of construction material with foundation construction Aggregate Class A and B : Rp .260.503,77 per M1 x 5500 = Rp . 1.432.770.735,00b . Construction costs by using foundation materials Cement Trade Base ( CTB ) : Rp . 176.361,84 Per M1 x 5500 = Rp. 969.990.120,00The second calculation of the cost of construction can be analyzed , that the construction of the foundation materials CTB can cut costs. So the difference in cost of construction happening isRp . 462.780.615,00Keywords : Value Engineering , CTB .